SOCIO-PHILOSOPHICAL ANALYSIS OF INCREASING WOMEN'S ACTIVITY IN SOCIETY - Raimova Sadoqat (Scholar Express Journal, 2022)
The article deals with the contradictions in gender issues, objective coverage of these conflicting aspects, important issues for science to discuss.
Keywords: Gender Inequality; Gender Roles; Discrimination; Patriarchal Relations